Jinhong decoction protects sepsis-associated acute lung injury by reducing intestinal bacterial translocation and improving gut microbial homeostasis - Bao, Kaifan; Wang, Meiling; Liu, Li; Zhang, Dongya; Jin, Cuiyuan; Zhang, Junfeng; Shi, Liyun (Frontiers in Pharmacology, 2023)
Background: Currently no specific treatments are available for sepsis and the associated syndromes including acute lung injury (ALI). Jinhong Decoction (JHD) is a traditional Chinese prescription, and it has been applied clinically as an efficient and safe treatment for sepsis, but the underlying mechanism remains unknown. The aim of the study was to explore the potential mechanisms of JHD ameliorating sepsis and concurrent ALI. Methods: The cecum ligation puncture (CLP)- induced murine sepsis model was established for determining the efficacy of JHD protecting CLP and ALI. The role of gut microbiota involved in the efficacy of JHD was evaluated by 16S rRNA sequencing and fecal microbiota transplantation (FMT). Translocation of intestinal Escherichia coli (E. coli) to lungs after CLP was verified by qPCR and in vivo-imaging. Intestinal permeability was analyzed by detecting FITC-dextran leakness. Junction proteins were evaluated by Western blotting and immunofluorescence. Results: JHD treatment remarkably increased survival rate of septic mice and alleviated sepsis- associated lung inflammation and injury. FMT suggested that the protective role for JHD was mediated through the regulation of gut microbiota. We further revealed that JHD administration partially restored the diversity and configuration of microbiome that was distorted by CLP operation. Of interest, the intestinal bacteria, E. coli particularly, was found to translocate into the lungs upon CLP via disrupting the intestinal mucosal barrier, leading to the inflammatory response and tissue damage in lungs. JHD impeded the migration and hence lung accumulation of intestinal E. coli, and thereby prevented severe ALI associated with sepsis. This effect is causatively related with the ability of JHD to restore intestinal barrier by up-regulating tight junctions. Conclusion: Our study unveils a mechanism whereby the migration of gut bacteria leads to sepsis- associated ALI, and we demonstrates the potential of JHD as an effective strategy to block this bacterial migration for treating sepsis and the associated immunopathology in the distal organs.